Stakeholder Involvement and Performance of Donor Funded Projects in Rwanda: A Case Study of Empowering Youth Through an Inclusive Cooperative Movement in Rwanda’ Project (eyicm) in Bugesera District - Emmanuel, Nshunguyinka (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2020)
This study aimed at examining the role of stakeholder’s involvement on performance of donor funded project in Rwanda. The role of stakeholder participation in project performance cannot be overlooked. A review of case studies has demonstrated a relationship between the two. The study undertook to demonstrate how stakeholder participation influences the performance of donor funded projects. The study considered stakeholders’ participation in three phases of the project cycle; initiation, planning and implementation. In assessing project performance, the study was limited to two (2) key project performance indicators; timely completion and cost implication. The study was guided by three objectives: identify the influence of stakeholder participation in project initiation on project performance, understand the influence of stakeholder participation in project planning on project performance and determine the influence of stakeholder participation in project implementation on project performance. The researcher studied EYICM Project in Bugesera District, which was co-funded by European Commission and Plan International. The respondents projected representatives from donors, representatives from the implementing agency, and the project beneficiaries. Data were collected using questionnaire from project beneficiaries and interview guide from donor and implementing agency representatives. The total sample size of 75 was used in the study. Descriptive design was used to analyze data; specifically, the researcher used SPSS and mainly measures of central tendency used to describe data. The researcher correlated the dependent and independent variables in order to test the relationship between the variables. The study expressed a significant relationship between stakeholders’ engagement in project initiation and project performance where r=0.064, p<0.01. in addition, the researcher found significant correlation between project acceptability by the community and performance of the project where r=-0.646, p<0.01. The outcome of the study will show the extent to which stakeholders involvement at all levels of project management cycle influences the performance of donor funded projects. As a result of investigation conducted through questionnaire and interview guide, the researcher discovered that most respondents confirmed stakeholders’ participation in project initiation with 49% strongly agree and 21% agree being involved in needs assessment; 36% strongly agree and 21% agree being involved in proposing solutions; 30% strongly agree and 36% agree being involved in setting project objectives. At the level of planning, 36% strongly agreed, 14% agreed that their engagement contributed to project acceptability by the community; 40% strongly agree, 30% agreed that it created the ownership of the project by the community and lastly, at implementation level, 40% strongly agreed, 28% agreed that it created the sense of ownership of project by the community while 38% strongly agreed, 32% agreed that it contributed to community empowerment. On the basis of the study findings, the researcher made the following conclusions; The role of stakeholders’ involvement on performance of donor funded project influenced performance of EYICM project in Bugesera District. Therefore, on the influence of project management factors on the EYICM project in Bugesera District, the study concluded that the adequate institutional management skills, donor contribution, positive government policies and institutional management practices aids the performance of the EYICM Project in Bugesera District in Rwanda.